The Linguistics of English Colonialism in Study Abroad: Translating the Study Abroad Experience for Language Minority Students (Comparative & International Education Series, 2021)
Decades of international education research has posited that English has been and will remain the de facto language of global research and study abroad opportunities, with recent studies suggesting English is the most widely used language by non-U.S. institutions to communicate with prospective study abroad students. However, considerable advances in computational linguistics, natural language processing, and the globalization of higher education renders it unnecessary for institutions of higher education to default their communication to English. As global higher education has massified, the English-centric nature of institutions of higher education around the world has minoritized English-language learners and those from languages minority groups, perpetuating English colonialism on linguistic terms.